Sosialisasi Perpajakan, Kesadaran Wajib Pajak, Perhitungan Tarif Pajak, dan Kepatuhan Pajak - Suartama, I Wayan Eka; Wiratmaja, I Dewa Nyoman (E-Jurnal Akuntansi, 2023)
The purpose of this study is to determine the effect of tax socialization, taxpayer awareness, and tax rate calculations on student tax compliance of Micro, Small and Medium Enterprises (MSMEs). This research was conducted at the Accounting Study Program, Faculty of Economics and Business, Udayana University, using saturated sampling. The number of samples in this study was 65 people, that is, the entire population of students in the 2014-2018 accounting study program who owned a business was taken as the sample. The analysis technique used is Multiple Linear Regression Analysis. The results of the study found that tax socialization had an effect on tax compliance. Taxpayer awareness affects tax compliance. Calculation of tax rates effect on tax compliance. This shows that the socialization of taxation, awareness of taxpayers and calculation of tax rates in MSMEs have an effect on increasing tax compliance of MSME students. Keywords: Socialization; Awareness; Tax Rates; Obedience